Social Innovation in Community-Based Household Waste Management in Ciamis Regency, West Java Province - Barsei, Adhityo Nugraha; Giyatno; Wahyuni, Nila; Atmoko, Andreo Wahyudi (Universitas Muhammadiyah Malang, 2023)
The Ciamis Regency Government, through the Office of Public Housing, Settlement Areas, and the Environment (DPRKPLH), has conducted the Selingkuh Mas Maggot program (Save the Community Environment, Manage Waste and Bank Maggot) as a social innovation in waste management. This study aims to analyze how the Ciamis District DPRKPLH and the community manage waste from the social innovation perspective. The method used in this study is qualitative, with in-depth interviews and literature studies. Data analysis was conducted through data coding, an open network, and a conclusion by using ATLAS.Ti software. The results of this study are that social innovation in Community-Based Waste Management in Ciamis Regency at least covers aspects of (1) drivers as a driving factor for the emergence of social innovation initiatives; (2) enablers, namely resources that support social innovation; (3) processes, where innovation and collaboration are key in implementation; and (4) outcomes, social innovation provides social, economic, and environmental benefits for the community.